Classifying Pervasive Games: On Pervasive Computing and Mixed Reality - Hinske, Steve; Lampe, Matthias; Magerkurth, Carsten; Röcker, Carsten (A reader for pervasive gaming research / Vol. 1. Concepts and technologies for pervasive games)
Pervasive Games have become popular in recent years. Their ambitious goal is to bring the computer into the world in order to augment existing games or to even come up with hitherto impossible or unthought-of forms of entertainment. This paper reflects on the various approaches to define what Pervasive Games consist of, how they relate to playing and games, and how different terms and views can be integrated. The paper contributes a unifying and integrating classification of the respective terms that relates different states of reality to the relevant dimensions and game elements.
Keywords: Pervasive Gaming Applications; User Interfaces; Smart Home Environments; Mixed Reality